Intraguild interactions between Euseius stipulatus and the candidate biocontrol agents of Tetranychus urticae in Spanish clementine orchards: Phytoseiulus persimilis and Neoseiulus californicus - Abad-Moyano, Raquel; Urbaneja, Alberto; Schausberger, Peter (2017)
Spanish clementine orchards are frequently infested by the two-spotted spider mte Tetranychus urticae. Natural control of T. urticae is insufficient despite the presence of Neoseiulus californicus and Phytoseiulus persimilis. The phytoseiid community is dominated by the generalist Euseius stipulatus which is poorly adapted to exploit T. urticae. Having the intention to promote biological control of T. urticae by augmentative releases we were interested whether P. persimilis and N. californicus are negatively affected by intraguild (IG) interactions with E. stipulatus. Two experiments were conducted. Firstly, we assessed female aggressiveness (quantified as combination of attack probability and latency) in IG predation on larvae. Secondly, we measured mortality, escaping rate and developmental time of immature IG prey in presence and absence of an adult IG predator female. Euseius stipulatus appeared the strongest IG opponent but microhabitat structure modulated the IG interactions and the advantage of E. stipulatus was partially offset when spider mite webbing was present. Implications of these IG interactions for natural and biological control of T. urticae in clementine orchards are discussed.